Analysis of Factors Influencing The Selection of Location on The Success of Micro-Small Service Business in Around Campus Unitri Malang, East Java, Indonesia - Costa, Fidel da (International Research & Development for Human Beings (IRDH), 2024)
This study aims to examine the effect of location selection on business success in small micro service businesses around the Unitri Malang Campus. Based on various literatures, many factors influence the choice of business location. However, location decisions often depend on the type of business, for retail and professional services businesses, the strategy used is focused on maximizing revenue. The main reason for the difference in location selection is the difference in the needs of each business. A good location is an individual matter when stated simply,